Mesenchymal Stem Cells in Veterinary Medicine—Still Untapped Potential - Magdalena Morawska-Kozłowska; Mateusz Pitas; Yauheni Zhalniarovich (Animals)
Mesenchymal stem cells (MSCs) hold significant therapeutic potential in veterinary medicine due to their regenerative and immunomodulatory properties. This review examines the clinical applications of MSCs across multiple animal species, including equine, canine, feline, and bovine medicine. MSC therapies have demonstrated promising outcomes in treating musculoskeletal disorders, osteoarthritis, inflammatory diseases, and tissue injuries, particularly in horses and dogs. In cats, MSCs show potential for managing chronic kidney disease, inflammatory bowel disease, and asthma, while in bovine medicine, they offer alternative treatment approaches for mastitis and orthopedic injuries. Despite these advancements, challenges such as treatment standardization, cell sourcing, and potential adverse effects, including tumorigenicity, remain under investigation. The emerging field of MSC-based veterinary medicine highlights its capacity to enhance healing, reduce inflammation, and improve clinical outcomes. However, further research is necessary to optimize treatment protocols and address safety concerns, ensuring the widespread adoption of MSC therapies in veterinary practice.